Gewerbliche Beleuchtung im Wohnquartier - eine unterschätzte nächtliche Belastung? Auschnitt aus einer Fallstudie als Diskussionsbeitrag. - Rehmann, Merlin (Universitätsverl. TU Berlin, 2014)
Der Band stellt einen Auszug aus einer Diplomarbeit im Studiengang Stadt- und Regionalplanung der TU Berlin dar. Die Arbeit untersucht die Konfliktlinien zwischen nächtlicher Beleuchtung durch Gewerbe- und Wohnnutzung aus Sicht der Stadtplanung in Form einer Fallstudie anhand eines Berliner Wohnquartiers. Aufbauend auf einer Erhebung aller Gewerbe und deren Beleuchtung zur Nachtzeit (22-6 Uhr) wurden Befragungen unterschiedlicher Beteiligter durchgeführt, deren Ergebnisse mit den Daten aus der Erhebung abgeglichen wurden.

This volume outlines core findings of the diploma thesis "Wohnen im Licht - Ab wann wird nächtliches Licht zur Last?" which was completed at the Institute of Urban and Regional Planning, TU Berlin in 2011/12. The work examines the conflicts between nocturnal lighting practices of local business owners versus residential land uses from the perspective of urban planning. It contains a contemporary case study from a residential neighborhood in the city of Berlin. Based on a survey of all the local businesses and their state of lighting at night time (10pm-6am) the author carried out interviews with different stakeholders. The comparison of the results with data and maps from the survey offers a useful and comprehensive pathway to identify key issues relating to nocturnal lighting emissions.
Conflicts between nocturnal lighting practices of local business owners versus residential land uses from the perspective of urban planning. Excerpt from a case study.
Keywords: Wohnungswesen; Wohnviertel; Gewerbe; Beleuchtung; Umweltbelastung; Nutzungskonflikt; Steuerung; Lichtverschmutzung